Answer :

The given expression is (3x + 2y)2 + (3x – 2y)2

We have,


(3x + 2y)2 = (3x)2 + 2.3x.2y + (2y)2(Here we apply standard identities)


= 9x2 + 12xy + 4y2


and


(3x-2y)2 = (3x)2-2.3x.2y + (2y)2


= 9x2-12xy + 4y2


Therefore,


(3x + 2y)2 + (3x – 2y)2 = 9x2 + 12xy + 4y2 + 9x2-12xy + 4y2


= 18x2 + 8y2


= 2(9x2 + 4y2)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

State whether theNCERT - Mathematics Exemplar

Fill in the blankNCERT - Mathematics Exemplar

What must be addeRD Sharma - Mathematics

Divide:

<p
RD Sharma - Mathematics

Divide:

<p
RD Sharma - Mathematics

Divide:

<p
RD Sharma - Mathematics